Modernization vs. vulgarization in online fashion luxury : how is internet impacting luxury brand equity ? - Marrão, Ana Rita Galante de Abreu (2016)
The Internet became an inherent part of people’s daily life and the major source of transformation in the relation between consumers and brands. However, in the luxury branding context, the introduction of prestige brands into a mass channel such as the Internet might bring the risk of vulgarization, loss of control over the brand, loss of the high-luxury appeal, jeopardizing brand equity. Hence, the present thesis paper proposes to answer the dilemma between the imperative of going online and the risk of luxury high-appeal dilution, by examining whether brand digital competence enhances the impact of advertising on the several dimensions of customer-based brand equity (CBBE) sources of luxury brands. Further, this study investigated the main impact of digital competence on CBBE as well as the risk of vulgarization by luxury going online. Additionally, it was tested if the impact of advertising on CBBE is mediated by the channel (online vs. offline) through which it is exposed to the consumers. To perform the study, a 2 (before the Advertising vs. after the advertising) x 2 (high digital competence vs. low digital competence) x 2 (online vs. offline) experiment was conducted and results were tested through MANOVA and ANOVA analysis. Around 250 international general consumers participated in the experiment though online questionnaire. The results show that consumers rated brands better in terms of awareness and image after being exposed to the brand advertising. The effect of advertising on brand image proved to be moderated by the level of brand digital competence, which means that, considering the same type of advertising, consumers will rate better a brand endowed with high digital competence than a brand endowed with low digital competence. However, this moderation effect does not apply in the case of brand awareness, which means that digital competence level does not affect the effectiveness of advertising in enhance brand awareness. Besides the analysis of the moderation effect, digital competence proved to be a very significant direct main effect on all the dimensions of the dependent variables Brand Awareness and Brand Image (excepting sensuality), which means that the effect of a brand digital competence goes much beyond the advertising activity. The ANOVA analysis on the online vs. offline channels demonstrated that there was a significant effect of advertising through online channels on awareness and significant effects on some dimensions of brand image such as love, uniqueness, positiveness of associations, quality and sensuality perception.